Higher Volume at Time of Breast Conserving Surgery Reduces Re-Excision in DCIS. (13th February 2011) - Wolf, J. H.; Wen, Y.; Axelrod, D.; Roses, D.; Guth, A.; Shapiro, R.; Cohen, J.; Singh, B.
Abstract : Purpose . The purpose of this study was to compare the surgical and pathological variables which impact rate of re-excision following breast conserving therapy (BCS) with or without concurrent additional margin excision (AM). Methods . The pathology database was queried for all patients with DCIS from January 2004 to September 2008. Pathologic assessment included volume of excision, subtype, size, distance from margin, grade, necrosis, multifocality, calcifications, and ER/PR status. Results . 405 cases were identified and 201 underwent BCS, 151-BCS-AM, and 53-mastectomy. Among the 201 BCS patients, 190 underwent re-excision for close or involved margins. 129 of these were treated with BCS and 61 with BCS-AM (P < .0001 ). The incidence of residual DCIS in the re-excision specimens was 32% (n = 65 ) for BCS and 22% (n = 33 ) for BCS-AM (P < .05 ). For both the BCS and the BCS-AM cohorts, volume of tissue excised is inversely correlated to the rate of re-excision (P = .0284 ). Multifocality (P = .0002 ) and ER status (P = .0382 ) were also significant predictors for rate of re-excision and variation in surgical technique was insignificant. Conclusions. The rate of positive margins, re-excision, and residual disease was significantly higher in patients with lower volume of excision. The performance of concurrent additional margin excision increases the efficacy of BCS for DCIS.